Notch Inhibition Enhances Cardiac Reprogramming by Increasing MEF2C Transcriptional Activity - Abad, Maria; Hashimoto, Hisayuki; Zhou, Huanyu; Morales, Maria Gabriela; Chen, Beibei; Bassel-Duby, Rhonda; Olson, Eric N. (Stem cell reports, 2017)
Conversion of fibroblasts into functional cardiomyocytes represents a potential means of restoring cardiac function after myocardial infarction, but so far this process remains inefficient and little is known about its molecular mechanisms. Here we show that DAPT, a classical Notch inhibitor, enhances the conversion of mouse fibroblasts into induced cardiac-like myocytes by the transcription factors GATA4, HAND2, MEF2C, and TBX5. DAPT cooperates with AKT kinase to further augment this process, resulting in up to 70% conversion efficiency. Moreover, DAPT promotes the acquisition of specific cardiomyocyte features, substantially increasing calcium flux, sarcomere structure, and the number of spontaneously beating cells. Transcriptome analysis shows that DAPT induces genetic programs related to muscle development, differentiation, and excitation-contraction coupling. Mechanistically, DAPT increases binding of the transcription factor MEF2C to the promoter regions of cardiac structural genes. These findings provide mechanistic insights into the reprogramming process and may have important implications for cardiac regeneration therapies. [Display omitted] •Notch activation is a barrier for GHMT-induced cardiac cell reprogramming•Notch blockade by DAPT improves GHMT-induced cardiac reprogramming•DAPT increases sarcomere organization, calcium flux, and beating in GHMT reprogramming•DAPT enhances transcriptional activity of MEF2C in GHMT reprogramming In this article, Olson and colleagues show that Notch signaling activation is a critical barrier for cardiac cell reprogramming. Notch signaling blockade by DAPT, a γ-secretase inhibitor, enhances fibroblast conversion to cardiomyocytes by increasing calcium flux, sarcomere structure, and beating. Mechanistically, Notch inhibition enhances the transcriptional activity of the cardiogenic transcription factor MEF2C, thereby enhancing expression of cardiac genes.